"The Variation of Productive Forces.": A Comment - Mixter, C. W. (Quarterly Journal of Economics, 1903)
Journal Article “The Variation of Productive Forces.” A Comment Get access C. W. Mixter C. W. Mixter Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 17, Issue 2, February 1903, Pages 332–334, https://doi.org/10.2307/1883669 Published: 01 February 1903